PERBEDAAN KADAR TANIN TOTAL EKSTRAK DAUN TURI (Sesbania grandiflora L.) VARIETAS MERAH DAN PUTIH DENGAN METODE SPEKTROFOTOMETRI UV-VIS - Kurniawati, Evi; Lestari, Tri Puji; Hardini, Pri Hardini (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2024)
Turi is one of the plants that has activity as an antimicrobial, antifungal, anti-inflammatory and antioxidant. The content of secondary metabolites in turi leaves are flavonoids, tannins, and alkaloids. Tannins are phenol compounds with hydroxy groups and several other groups such as carboxyl. This study aims to determine the difference in total tannin levels in turi leaf extracts of red and white varieties. The extraction process with maceration using 70% ethanol solvent. Then the extract obtained was carried out screening tests, thin layer chromatography tests, and determination of tannin levels by UV-Vis spectrophotometry. Parameters of analytical method validation were carried out by determining linearity, accuracy, precision, LOD and LOQ. The results of the validation of the linearity analysis method obtained a linear regression equation y = 0.0038x + 0.3153 r value = 0.9985. The accuracy results obtained are in the range of 97-103%, RSD value of 0.18% and the LOD value is 6,213 ppm and LOQ is 20,711 ppm. The measurement results of total tannin content in turi leaf extracts of red and white varieties at a wavelength of 750 nm are 7.876% w / w TAE and 9.195% w / w TAE, respectively. Independent sample T-test results show there is a significant difference (p < 0.05) in the total tannin content of turi leaf extracts of red and white varieties. Keywords: Turi leaves, tannin, UV-vis spectrophotometer